Development of monitoring techniques and validation of the acidity level of biofloc pond water for optimizing tilapia aquaculture. Issue 1 (1st April 2022) - Prakosa, Jalu A.; Purwowibowo; Widiyatmoko, Bambang; Suryadi; Setiono, Andi; Rofianingrum, Mefina Y.; Maftukhah, Tatik; Afandi, Mohamad I.; Mulyanto, Iman; Pratomo, Hari
Abstract: The water's acidity level will impact the water's suitability for fish survival. Fish waste and food residue, on the other hand, can reduce the acidity of the water and produce toxic ammonia, which is damaging to fish. Biofloc technology (BFT) can transform toxic ammonia into floc protein, which can be used as an alternative diet. However, the acidity of the pond water must be monitored to ensure that biofloc techniques are implemented successfully. Tilapia is a popular fish among Indonesians, although it is difficult to farm using biofloc technology, which is important for public food preservation. This research aims to build technology for monitoring and validating waters acidity levels in tilapia biofloc ponds. Observing the quality of pool water acidity is carried out automatically through a microcontroller. The pH powder calibrator provides accurate validation of water acidity sensor measurements. The monitoring results of pH by around 7.38±0.15 showed that the average level of acidity of the biofloc water was still following the pH tolerance of Tilapia. This proposed monitoring method is highly beneficial for supporting national food security through BFT fisheries, particularly to avoid the mass mortality of Tilapia because of poor water acidity conditions.